Converting the equation into a^{2}+2ab+b^{2 }form, we get,

⇒ (2x)^{2} + 2 × 2x × \( \sqrt{3}\) + \( \sqrt({3})^2\) = 0

⇒ (2x + \( \sqrt{3}\))^{2} = 0

⇒ (2x + \( \sqrt{3}\)) = 0 and (2x + \( \sqrt{3}\)) = 0

Therefore, either \( x = \dfrac{\sqrt{3}}{2}or\; x = \dfrac{\sqrt{3}}{2}\)

Answered by Pragya Singh | 1 year agoA natural number when increased by 12 equals 160 times its reciprocal. Find the number.

Find a natural number whose square diminished by 84 is equal to thrice of 8 more than the given number.

The numerator of a fraction is 3 less than the denominator. If 2 is added to both the numerator and the denominator, then the sum of the new fraction and the original fraction is \( \dfrac{29}{20}\) Find the original fraction.

The sum of the squares of two consecutive even numbers is 340. Find the numbers.

The sum of the squares of two consecutive multiple of 7 is 637. Find the multiples.